A COMPARISON OF PLACEMENT IN FIRST-YEAR UNIVERSITY MATHEMATICS COURSES USING PAPER AND ONLINE ADMINISTRATION OF A PLACEMENT TEST. Issue 3 (October 2008) - Schumacher, Phyllis A.; Smith, Richard M.
No abstract available